Resource optimization of secure energy efficiency based on mmWave massive MIMO-NOMA system with SWIPT - Fei ZHAO; Wanming HAO; Gangcan SUN; Yiqing ZHOU; Fei WANG; Yi WANG (Tongxin xuebao)
The secure energy efficiency (SEE) problem was investigated for the millimeter wave (mmWave) multiple input multiple output (MIMO) non-orthogonal multiplex access (NOMA) systems with simultaneous wireless information and power transfer (SWIPT) in the presence of multiple legitimate receiver (LR) and an eavesdropper.LR was first grouped according to the channel state information and the cluster heads of each group were selected,then the LR of each cluster was served by each beam with NOMA and hybrid precoding technology.Based on this,a SEE maximization problem was formulated by optimizing power allocation and power splitting factors.The Dinkelbach algorithm and first order Taylor approximation were proposed to transform the original non-convex problem into a convex one,and an iterative algorithm was developed to solve it.Finally,numerical results show that the proposed scheme can effectively improve the SEE.